Digital Transformation of Islamic Banks through E-Business to Support Green Banking Principles - Dea Riyanti Paramitha; Muhamad Iqbal Fasa (Denasya Smart Publisher, 2025)
The digital transformation of Islamic banking through e-business has become a key strategy for enhancing operational efficiency and expanding financial service accessibility. Digitalization enables Islamic banks to adopt technologies such as mobile banking, artificial intelligence, and big data analytics to improve service quality and compliance with Sharia principles. Additionally, the Green Banking concept is reinforced through paper reduction, energy efficiency, and environmentally friendly investments. However, challenges such as regulations, infrastructure, and digital literacy remain significant obstacles. Therefore, solutions such as digital financial education, collaboration with Islamic fintech, and strengthening policies and digital security are needed to ensure the sustainability of this transformation. With the right strategies, the digitalization of Islamic banking can support sustainable economic growth while remaining aligned with Islamic principles.